Sun: the great ball of fire - Mukherjee, Vijita (New Delhi The Energy Resources Institute, 2013)
The big, bright sun is just another star! Really, it is true! Did you know that its rays are full of packets of energy? And that there are many clever ways in which people around the world are using this energy? Read all about what happens inside the sun and all that it does for us.
Keywords: Sun; Energy